2014
DOI: 10.3892/mco.2014.369
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genetic polymorphism, serum lipoprotein levels and breast cancer risk: A case-control study

Abstract: The purpose of this study was to evaluate the association between apolipoprotein E (APOE) allelic frequency, serum lipoproteins and breast cancer (BC). We conducted a nested case-control study within a cohort including 47 cases and 165 controls. Polymerase chain reaction-restriction fragment length polymorphism analyses of the APOE polymorphism were performed. In general, participants with the genotype including alleles e2 and e3 tended to have lower serum triglycerides, total cholesterol and low-density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…This is consistent with previous work showing that Ab is more strongly expressed by breast cancer cells lines that have increased metastatic potential [42]. Our findings support those of previous studies suggesting that APOE genotype may be a valuable predictor of risk for breast cancer [48] as well as breast cancer-related cognitive impairment [31,32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous work showing that Ab is more strongly expressed by breast cancer cells lines that have increased metastatic potential [42]. Our findings support those of previous studies suggesting that APOE genotype may be a valuable predictor of risk for breast cancer [48] as well as breast cancer-related cognitive impairment [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…Increased risk for breast cancer diagnosis has been associated with the APOE ɛ4 genotype [48]. We conducted a post hoc, two-tailed Spearman correlation analysis that demonstrated a small effect association between APOE ɛ4 genotype and higher disease stage (r = 0.21, P  = .067).…”
Section: Discussionmentioning
confidence: 99%
“…Of 530 potentially relevant articles identified according to our search strategy, 25 articles that examined the associations of APOE gene ε2/ε3/ε4 polymorphism with either cancer risk (n = 22) or circulating lipid changes (n = 4) were eligible according to the predefined inclusion and exclusion criteria 5 7 8 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 . The first article was published in 1996 10 .…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced, this capability was proven to be defective for the ε2 allele with its carriers exhibiting lower circulating cholesterol level and higher triglyceride level when compared with ε3 homozygotes; in contrast, circulating total cholesterol and low-density lipoprotein cholesterol appear to be higher in those with ε4 allele 6 . In spite of exhaustive investigations, published data on the associations between APOE gene ε2/ε3/ε4 polymorphism and cancer risk are conflicting and inconclusive 5 7 8 9 . A recent meta-analysis by Anand et al who examined this association in 16 studies failed to detect any positive signal except in cohort studies 9 .…”
mentioning
confidence: 99%
“…High levels of APOA1 were associated with higher incidence rates of breast cancer (22), while another study indicated an inverse correlation between APOA1 levels and breast malignancies (23). Serum APOE may play diverse roles in several biological processes and reports show that it is up-regulated in various malignancies, including breast cancer, possibly acting as a defense mechanism (24,25). Xu et al not only showed that serum APOE levels were elevated in patients with breast cancer compared to healthy controls, which is in line with our own results, but also that patients with high serum APOE levels had a worse prognosis, indicating that serum APOE could be an independent prognostic variable for breast cancer (26).…”
Section: Serum Samples From Patients With Male Breast Cancer (A) and mentioning
confidence: 99%